Biochemical Distribution of Tau Protein in Synaptosomal Fraction of Transgenic Mice Expressing Human P301L Tau - Sahara, Naruhiko; Murayama, Miyuki; Higuchi, Makoto; Tetsuya, Suhara; Takashima, Akihiko (Frontiers in Neurology, 2014)
Alzheimer’s disease is a progressive dementia that is characterized by a loss of recent memory. Evidence has accumulated to support the hypothesis that synapses are critical storage sites for memory. However, it is still uncertain whether tau protein is involved in associative memory storage and whether tau is distributed in mature brain synapses. To address this question, we examined the synaptosomal distribution of tau protein in both JNPL3 transgenic mice expressing human P301L tau and non-transgenic littermates. The JNPL3 mouse line is known as one of the mouse models of human tauopathy that develop motor and behavioral deficits with intracellular tau aggregates in the spinal cord and brainstem. The phenotype of disease progression is highly dependent on strain background. In this study, we confirmed that male JNPL3 transgenic mice with C57BL/6J strain background showed neither any sign of motor deficits nor accumulation of hyperphosphorylated tau in the sarkosyl-insoluble fraction until 18 months of age. Subcellular fractionation analysis showed that both mouse tau and human P301L tau were present in the synaptosomal fraction. Those tau proteins were less phosphorylated than tau in the cytosolic fraction. Human P301L tau was preferentially distributed in the synaptosomal fraction while mouse endogenous tau was more distributed in the cytosolic fraction. Interestingly, a human-specific tau band with phosphorylation at Ser199 and Ser396 was observed in the synaptosomal fraction of JNPL3 mice. This tau was not identical to either tau species in cytosolic fraction or a prominent hyperphosphorylated 64 kDa tau species that was altered to tau pathology. These results suggest that exogenous human P301L tau induces synaptosomal distribution of tau protein with a certain phosphorylation. Regulating the synaptosomal tau level might be a potential target for a therapeutic intervention directed at preventing neurodegeneration.